Centimetre-wave continuum radiation from the rho Ophiuchi molecular cloud - Casassus, S; Dickinson, C; Cleary, K; Paladini, R; Etxaluze, M; Lim, T; White, G; Burton, M; Indermuehle, B; Stahl, O; Roche, P (2008)
The ρ Oph molecular cloud is undergoing intermediate-mass star formation. Ultraviolet radiation from its hottest young stars heats and dissociates exposed layers, but does not ionize hydrogen. Only faint radiation from the Rayleigh-Jeans tail of ∼10-100 K dust is expected at wavelengths longwards of ∼3 mm. Yet cosmic background imager (CBI) observations reveal that the ρ Oph W photodissociation region is surprisingly bright at centimetre wavelengths. We searched for interpretations consistent with the Wilkinson Microwave Anisotropy Probe radio spectrum, new Infrared Space Observatory-Long Wavelength Spectrograph (LWS) parallel mode images and archival Spitzer data. Dust-related emission mechanisms at 1 cm, as proposed by Draine and Lazarian, are a possibility. But a magnetic enhancement of the grain opacity at 1 cm is inconsistent with the morphology of the dust column maps Nd and the lack of detected polarization. Spinning dust, or electric-dipole radiation from spinning very small grains (VSGs), comfortably explains the radio spectrum, although not the conspicuous absence from the CBI data of the infrared circumstellar nebulae around the B-type stars S1 and SR3. Allowing for VSG depletion can marginally reconcile spinning dust with the data. As an alternative interpretation, we consider the continuum from residual charges in ρ Oph W, where most of carbon should be photoionized by the close binary HD 147889 (B2IV, B3IV). Electron densities of ∼102 cm-3, or H-nucleus densities nH > 106 cm-3, are required to interpret ρ Oph W as the C ii Strömgren sphere of HD 147889. However, the observed steep and positive low-frequency spectral index would then imply optically thick emission from an hitherto unobserved ensemble of dense clumps or sheets with a filling factor of ∼10-4 and nH ∼ 107 cm-3. © 2008 Universidad de Chile. Journal compilation © 2008 RAS.